Applications of laser‐induced breakdown spectroscopy for soil characterization, part II: Review of elemental analysis and soil classification. (8th January 2020) - Villas‐Boas, Paulino R.; Franco, Marco A.; Martin‐Neto, Ladislau; Gollany, Hero T.; Milori, Debora M. B. P.
Abstract: In‐field soil health assessments, including plant nutrients and toxic elements, are needed and could improve the sustainability of agriculture production. Among the available analytical techniques for these analyses, laser‐induced breakdown spectroscopy (LIBS) has become one of the most promising techniques for real‐time soil analysis at low cost and without the need for reagents. The first part of this two‐part review (Part I, Villas‐Boas, P.R., de Franco, M.A., Gollany, H.T., Martin‐Neto, L. & Milori, D.M.B.P. 2019. Applications of laser‐induced breakdown spectroscopy for soil characterization, Part I: Review of Fundamentals and Chemical and Physical Properties.) in this issue focused on the fundamentals of LIBS for soil analysis and its use for soil chemical and physical characterization. Our objectives in this review article (Part II) are to review (a) the main applications of LIBS in the determination of soil carbon (C), nutrients and toxic elements, spatial elemental mapping, and (b) its use in soil classification. Traditional and more recent techniques will be compared to LIBS, considering their advantages and disadvantages. Laser‐induced breakdown spectroscopy is a promising, versatile technique for detecting many elements in soil samples, requires little or no sample preparation, takes only a few seconds per sample, and has a low cost per sample compared to other techniques. However, overcoming matrix effects is a challenge for LIBS applications in soil analysis, because most studies are conducted with limited changes in the matrix. In spite of the limitation of matrix effects, a typical LIBS system has a limit of detection of 0.3, 0.6, 4, 7, 10, 18, 46 and 89 mg kg −1 for Mo, Cu, Mg, Mn, Fe, Zn, K and Ca, respectively. Laser‐induced breakdown spectroscopy holds potential for real‐time in‐field spatial elemental analysis of soils and practical applications in precision farming with proper calibration. This could lead to immediate diagnoses of contaminated soil and inefficient nutrient supplies and facilitate well‐informed soil management, increasing agricultural production while minimizing environmental impacts. Highlights: Laser‐induced breakdown spectroscopy (LIBS) is a fast analytical technique with great potential for elemental mapping of soils. Elemental analyses of soil and plants and soil classification by LIBS are reviewed. Soil and rhizosphere spatial elemental analyses by LIBS are presented. LIBS advantages, limitations and challenges are discussed for soil elemental analysis.